2016
DOI: 10.17645/mac.v4i3.525
|View full text |Cite
|
Sign up to set email alerts
|

Cyberbullying, Race/Ethnicity and Mental Health Outcomes: A Review of the Literature

Abstract: Cyberbullying is a relatively new phenomenon associated with the widespread adoption of various digital communication technologies, including the internet and mobile phones. As of 2013, nearly 20% of youths in grades 9-12 in the US reported being traditionally bullied in face-to-face encounters while almost 15% reported being cyberbullied (Kann et al., 2014). Bullying victimization is associated with a variety of behavioral and psychological effects, from becoming bullies themselves (i.e., bully-victims), to p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
28
2
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(35 citation statements)
references
References 50 publications
(100 reference statements)
3
28
2
1
Order By: Relevance
“…The remaining topics obtained less than 10%. In general terms, this discovery coincides with research in this regard: sexual relationships (sex, pregnancy), all that surrounds harmful substances (alcohol or drugs, among others) and bullying are the topics of main interest for adolescents (Livingstone et al, 2014;Barry et al, 2015;López-Vidales & Gómez-Rubio, 2015;Edwards, Kontostathis, & Fisher, 2016;Yarosh et al, 2016;;Álvarez-García et al, 2017).…”
Section: The Samplesupporting
confidence: 66%
“…The remaining topics obtained less than 10%. In general terms, this discovery coincides with research in this regard: sexual relationships (sex, pregnancy), all that surrounds harmful substances (alcohol or drugs, among others) and bullying are the topics of main interest for adolescents (Livingstone et al, 2014;Barry et al, 2015;López-Vidales & Gómez-Rubio, 2015;Edwards, Kontostathis, & Fisher, 2016;Yarosh et al, 2016;;Álvarez-García et al, 2017).…”
Section: The Samplesupporting
confidence: 66%
“…Literature on cyberbullying continues to grow, with rates varying according to a number of factors, including age, gender, and ethnicity. [6][7][8] The present study used a large national sample of adult New Zealanders between the ages of 18 and 97 years, with a unique sampling of ethnic groups, contrasting men and women. With regard to age cohorts, the results indicate that cyberbullying is most prevalent among young adults (18-25 years), 40.5 percent of whom reported personal experience of this phenomenon during their lifetime.…”
Section: Discussionmentioning
confidence: 99%
“…Cyberbullying, popularized as ''virtual abuse,'' is defined as intentionally aggressive behavior 3 that is implemented via digital communication such as e-mail, text messages, or mobile phone. [4][5][6] Many studies note that it has been linked to a host of negative outcomes at both the physical and psychological levels. 7 One meta-analysis of 131 studies suggests that increased stress, loneliness, and dependence on alcohol were among the outcomes of such experiences.…”
Section: Introductionmentioning
confidence: 99%
“…Their results highlight that Latinx respondents' depression and anxiety levels were positively linked to cybervictimization and that they were strengthened by low levels of school attachment. On their side, Edwards et al (2016) show that Latinx adolescent cybervictims revealed more suicidal ideation, depression, and suicidal behaviors than their Asian and Caucasian counterparts. Sexual minority youth are also notably vulnerable groups in terms of victimization (Kosciw et al, 2016;Elipe et al, 2018).…”
Section: Cybervictimization and Well-being Of Children And Young Peoplementioning
confidence: 95%